Simplify
Simplify expression - which expression is equivalent to:
3(m + 2) − 4(2m − 9)
3(m + 2) − 4(2m − 9)
Correct answer:
![](/img/85/expr_3.jpg)
Tips for related online calculators
Do you have a linear equation or system of equations and are looking for its solution? Or do you have a quadratic equation?
You need to know the following knowledge to solve this word math problem:
Related math problems and questions:
- Which 7
Which choice is NOT equivalent to the following expression? 9 x { [ 14 ÷ 2 + (4-1) ] - 8 } A 9 x { 10 - 8 } B 9 x { [ 14 ÷ 2 + 3] - 8 } C 9 x 10 - 8 D 18
- Consider 2
Consider the following formula: y = 3 ( x + 5 ) ( x - 2 ). Which of the following formulas is equivalent to this one? A. Y=3x²+9x-30 B. Y=x²+3x-10 C. Y=3x²+3x-10 D. Y=3x²+3x-30.
- Simplify:
Simplify: 8(−9 − 5x) + 4b use x = 9 and b = −9
- Equivalent expression 3
Ariel needs to calculate 12×8-6×8. Which expression will give Ariel the same answer? A.8×(12-6) B.8×(12-8) C.(12×6)-(8×8) D. (12×6)-(8+8)
- Which 4
Which number is equivalent to 5×10+4×1+8×110+6×1100+1×11,000?
- Equivalent equation
Which equation, when solved, results in a different value of x than the other three? A. - (7)/(8) x - (3)/(4) = 20 Negative 7/8 x minus three-fourths = 20 B. (3)/(4) + (7)/(8) x= -20 Three-fourths + 7/8 x = negative 20 C. - 7 (1)/(8)x - 3/4 = 20 Negat
- Simplify 2
Simplify expression: 5ab-7+3ba-9